Teknik Gores Aksara Arab pada Naskah Berbahan Lontar di Pesantren Suryalaya - Trie Utari Dewi (Center for Research and Development of Religious Literature and Heritage, Agency for Research and Development and Training, Ministry of Religious Affairs of the Republic of Indonesia, 2014)
The thesis aims to reveal the scratch technique which is used by the scriptwriter of Ali 'Imran made of palm-leaf in Pesantren Suryalaya, tasikmalaya. If it is viewed from the physical aspects of palm-leaf manuscript material, the writing of Ali 'Imran script which uses Arabic script is considered very difficult because the material is thin and easily torn.In addition, the character of the Arabic alphabet which is curved and flexible would be difficult inscribed on palm-leaf material, in contrast to the other palm-leaf manuscripts as ancient Javanese or Sundanese which have upright and rigid characters. To reveal the scratch technique used by writers in the Arabic script to write on palm-leaf material, it is needed to know the various types of Arabic script or the types of Khatt and its characters. After that, it is compared between the Arabic scripts on the manusript with the type of Khatt that resembles the script. The result is the Arabic alphabet script on the Ali 'Imran script has some aspects that resemble written characters riq'ah Khatt, so some scratch techniques used on the Ali ‘Imran manuscript is used in the technique of writing Khatt riq'ah with the addition of distinctive technique adapted to manuscript materials.Keywords: Technique, Scratch, Arabic script, Palm-leaf Manuscript.